VEGFA, FLT1, KDR and colorectal cancer: Assessment of disease risk, tumor molecular phenotype, and survival. Issue 1 (21st June 2013) - Slattery, Martha L.; Lundgreen, Abbie; Wolff, Roger K.; DiGiovanni, John
Abstract Angiogenesis is essential for tumor progression. Vascular endothelial growth factor (VEGFA) and its receptors 1 (FLT1) and 2 (KDR), have been identified as major mediators of this process. We hypothesized that genetic variation in FLT1 (38 SNPs), KDR (22 SNPS), and VEGFA (11 SNPs) would be associated with colon and rectal cancer development and survival. Data from a case–control study of 1555 colon cancer cases and 1956 controls and 754 rectal cancer cases and 959 controls were used. An adaptive rank truncation product (ARTP), based on 10 000 permutations, was used to determine the statistical significance of the candidate genes and angiogenesis pathway. Based on ARTP results, FLT1 was significantly associated with risk of colon cancer (PARTP = 0.045) and VEGFA was significantly associated with rectal cancer (PARTP = 0.036). After stratifying by tumor molecular subtype, SNP associations observed for colon cancer were: VEGFA rs2010963 with CIMP+ colon tumors; FLT1 rs4771249 and rs7987649 with TP53; FLT1 rs3751397, rs7337610, rs7987649, and rs9513008 and KDR rs10020464, rs11941492, and rs12498529 with MSI+ and CIMP+/KRAS2‐mutated tumors. FLT1 rs2296189 and rs600640 were associated with CIMP+ rectal tumors and FLT1 rs7983774 was associated with TP53‐mutated rectal tumors. Four SNPs in FLT1 were associated with colon cancer survival while three SNPs in KDR were associated with survival after diagnosis with rectal cancer. Aspirin/NSAID use, smoking cigarettes, and BMI modified the associations. These findings suggest the importance of inflammation and angiogenesis in the etiology of colorectal cancer and that genetic and lifestyle factors may be targets for modulating disease risk. © 2013 Wiley Periodicals, Inc.